THE VERIFICATION OF DATA OF MEASUREMENTS AT THE CREATION OF SKY SURVEY CATALOGUES WITH AUTOMATIC MEASURING MACHINES PARSEC - Sergeeva, T. P. (Одеські астрономічні публікації, 2017)
The system of an automatic control and the data verification in real time at the measurements with the automatic measuring machines PARSEC, had been developed to obtain the best accuracy, reliability and certainty of the results of the measurements and the high productivity in the same time. The principles and methods which had been used as a baseof the developed system are presented in this paper.